2015
DOI: 10.1002/jgt.22000
|View full text |Cite
|
Sign up to set email alerts
|

A Reconfigurations Analogue of Brooks' Theorem and Its Consequences

Abstract: Let G be a simple undirected connected graph on n vertices with maximum degree . Brooks' Theorem states that G has a proper -coloring unless G is a complete graph, or a cycle with an odd number of vertices. To recolor G is to obtain a new proper coloring by changing the color of one vertex. We show an analogue of Brooks' Theorem by proving that from any k-coloring, k > , a -coloring of G can be obtained by a sequence of O(n 2 ) recolorings using only the original k colors unless -G is a complete graph or a cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 41 publications
0
62
0
Order By: Relevance
“…Conjecture has resisted some efforts and has only been verified (other than for trees) for graphs with degeneracy at least normalΔ1 where normalΔ denotes the maximum degree of the graph . It is also known to hold if degeneracy is replaced by tree‐width .…”
Section: Introductionmentioning
confidence: 99%
“…Conjecture has resisted some efforts and has only been verified (other than for trees) for graphs with degeneracy at least normalΔ1 where normalΔ denotes the maximum degree of the graph . It is also known to hold if degeneracy is replaced by tree‐width .…”
Section: Introductionmentioning
confidence: 99%
“…The results on connectivity also showed quadratic bounds on diameter, including a lower bound on diameter for chordal graphs, culminating in the proof of the conjecture for k ≥ tw(G) + 2 [85]. Subsequently, the conjecture was proved for k = ∆(G) + 1 and ∆(G) ≥ 3; in this case, the reconfiguration graph consists of isolated vertices and one more component, with diameter O(|V(G)| 2 ) [81]. It was further observed that by increasing the number of colors, it is possible to obtain linear diameter, in particular, for every k ≥ 2col(G) + 2 [86].…”
Section: K-coloring Reconfigurationmentioning
confidence: 92%
“…Subsequently, the conjecture was proved for k = ∆(G) + 1 and ∆(G) ≥ 3; in this case, the reconfiguration graph consists of isolated vertices and one more component, with diameter O(|V(G)| 2 ). [81]. It was further observed that by increasing by number of colors, it is possible to obtain linear diameter, in particular, for every k ≥ 2col(G) + 2 [86].…”
Section: K-coloring Reconfigurationmentioning
confidence: 97%
“…Recall that the degeneracy, col(G), is the largest minimum degree of any subgraph of G; the degeneracy of G is an upper bound on its maximum degree, and the treewidth of G, tw(G), is an upper bound on col(G). More precisely, for any connected graph that is not regular, col(G) = ∆(G) − 1 [81], and the chromatic number is at most one greater than the degeneracy. Yet another property of use is the Grundy number, χ g (G), defined as the largest possible number of colors used by a greedy coloring of G; χ g (G) ≤ ∆(G) + 1.…”
Section: K-coloring Reconfigurationmentioning
confidence: 99%
See 1 more Smart Citation